Report on State Tube Wells (Uttar Pradesh) - Planning Commission (Planning Commission, 1961)
The State of Uttar Pradesh comprising 1,13,410 square miles of area lies in a climatic belt, which can be best described as monsoon-tropical. It has three pronounced seasons, namely a cold period from October to February with temperature ranging from 10° to 27°C. (50° to 80°F.), a hot season from March to mid-June with temperature from 38° to 46° C. (100° to 115°F.) and a wet monsoon period from mid-June to September with warm temperature generally around 32°C. (9O°F.) and humidity from 60 to 80 percent. Practically all rain falls during the monsoon period. It varies from 20 inches to 60 inches, gradually increasing from West to East, and is far higher in the extreme North, where it is augmented by air currents rising against Himalayan range.
Committee on Plan Projects Minor Irrigation Team
Committee on Plan Projects Minor Irrigation Team